Francis Bacon : 'Taking Reality by Surprise' - Domino, Christophe; Translated by Sharman, Ruth (London Thames & Hudson Ltd., 2007)
A detailed study of Francis Bacon - the man and the artist - looking at his influence on 20th-century art and providing a fascinating insight into his childhood, influences, intentions, methods and sources. This book presents his work in six fold-outs of his triptychs.
Include colour illustrations and index
Keywords: Figurative painting, English -- Bacon, Francis, 1909-1992 -- Painting, British